The Consumers Characteristics Analysis of Low Temperature Home Delivery - Shu-Fang Lai (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2013)
Because of technological advancements and the popularity of the Internet, online shopping has become an important shopping channel for consumers. Because people increasingly eat out, more consumers shop online, and food products are collected from convenience stores, or frozen food home delivery services are used. This study used questionnaire surveys to analyze the consumption habits of residents who shop online for frozen foods in the urban areas of northern Taiwan (Taipei City and New Taipei City). We distributed and collected 548 questionnaires, of which 484 were valid. Descriptive statistics, a chi-square test, and logistics regression analysis were used to analyze consumer characteristics, as well as important influential factors. The research results indicated that most online shoppers were women, and the top 3 factors influencing their purchasing decisions were freshness, delivery convenience, and ordering convenience. Participants in the age group of 40-49 years old, living in the urban area of New Taipei City, without junior college education, and with less than 10,000 NTD monthly incomes, were less likely to purchase frozen foods using low-temperature logistics services.